Retroperitoneal bronchogenic cyst: a case report and literature review - Jiang, Bohao; Xie, Tiantian; Hu, Jiyuan; Xu, Yitong; Zhang, Hao (Frontiers in Oncology, 2024)
IntroductionRetroperitoneal bronchogenic cyst, typically situated in the subdiaphragmatic region, is a rare congenital benign developmental abnormality arising from dysplasia of the foregut and abnormal budding of the tracheobronchial tree. Due to its low incidence, there are limited reports regarding this condition.Case presentationFour retroperitoneal bronchogenic cysts near the left adrenal gland were identified without accompanying clinical symptoms. One case was misdiagnosed as an adrenal tumor prior to surgery, while the others were diagnosed as retroperitoneal cysts of uncertain origin. All cases underwent surgical resection, with three being performed laparoscopically and one utilizing robot-assisted techniques. Pathological reports confirmed the diagnosis of bronchogenic cyst in each instance. The prognosis was favorable for all four patients, with no complications or recurrences observed. Additionally, a literature review was conducted, encompassing 82 cases, which revealed similar characteristics and radiological manifestations in the majority of cases.ConclusionAlthough retroperitoneal bronchogenic cysts are rare developmental malformations lacking distinctive clinical and radiological features, reported cases exhibit similarities in certain clinical and imaging characteristics. This report offers additional insights into the diagnosis and management of this rare disease. Future reports are essential to enhance understanding of this disease.